Arah Politik Majelis Ulama Indonesia (MUI) Serta Pandangan Terhadap Relasi Agama Dan Negara - M. Fakhrul Mahdi; Rizqa Febry Ayu (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2023)
Abstract: The aim of this research is the early history of the formation of the MUI and it is political direction as well as how the MUI views the relationship between religion and the state in national and state life in the country. This article uses a normative and historical juridical approach, the researcher uses descriptive qualitative techniques, namely research based on explanations of the problems regarding the object being studied through analysis and so on. The result of the research are that the MUI’S views on the relationship between religion and the state are reflected in every discourse and attitude of the MUI itself, both through fatwas and decisions issued by the MUI. MUI views that Pancasila as the basic, philosophy and ideology of the nation and state is the rope that binds all citizens of the nation in establishing relations between fellow citizens of the nation. The MUI’s political direction began to be oriented towards the religionizaion of politics in the sense of unification of din wa siyasah, meaning that there is a reciprocal relationship between Islam and the state. The state is a vechile for realizing Islamic values such as justice, humanity and peace. Meanwile, the state needs Islam as a foundation for the development of an advanced and moral society and rejects the separation between religion and state.Abstrak: Tujuan dari penelitian ini adalah bagaimana sejarah awal pembentukan MUI dan arah politiknya serta bagaimana MUI memandang relasi agama dan negara didalam kehidupan berbangsa dan bernegara di tanah air. Artikel ini menggunakan pendekatan yuridis normatif serta historis, penelitian menggunakan teknik kualitatif deskriptif, yaitu penelitian berdasarkan penjelasan-penjelasan dari permasalahan terhadap objek yang dikaji dengan analisa dan lain-lain. Hasil penelitian yaitu pandangan MUI tentang relasi agama dan negara tercermin dari setiap wacana dan sikap MUI itu sendiri, baik melalui fatwa maupun keputusan yang dikeluarkan oleh MUI. MUI memandang bahwa Pancasila sebagai dasar, falsafah dan ideologi berbangsa dan bernegara merupakan tali pengikat seluruh warga bangsa dalam menjalin relasi antar sesama warga negara bangsa. Arah politik MUI mulai berorientasi pada agamaisasi politik dalam arti penyatuan din wa siyasah, artinya bahwa terdapat hubungan timbal balik antara Islam dan Negara. Negara sebagai wahana mewujudkan nilai Islam seperti keadilan, kemanusiaan dan perdamaian. Sedangkan Negara memerlukan Islam sebagai landasan bagi pembangunan masyarakat yang maju dan berakhlak serta menafikan pemisahan antara agama dan negara.